2022
DOI: 10.3390/ijerph19031645
|View full text |Cite
|
Sign up to set email alerts
|

17 Is the New 15: Changing Alcohol Consumption among Swedish Youth

Abstract: To examine and compare trends in drinking prevalence in nationally representative samples of Swedish 9th and 11th grade students between 2000 and 2018. A further aim is to compare drinking behaviours in the two age groups during years with similar drinking prevalence. Data were drawn from annual surveys of a nationally representative sample of students in year 9 (15–16 years old) and year 11 (17–18 years old). The data covered 19 years for year 9 and 16 years for year 11. Two reference years where the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…Many of our findings align with previous research aimed at understanding the decline in youth drinking. For example, quantitative studies have demonstrated that alcohol use is starting later in more recent cohorts [46‐48], and our findings indicate that delayed uptake has occurred in NZ as well as the US, Australia and Sweden. Our findings are also consistent with previous qualitative studies that have highlighted increasing awareness of the health risks of drinking, and the rise of ‘healthism’ in which health is positioned as a personal responsibility and a moral imperative [28,32].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Many of our findings align with previous research aimed at understanding the decline in youth drinking. For example, quantitative studies have demonstrated that alcohol use is starting later in more recent cohorts [46‐48], and our findings indicate that delayed uptake has occurred in NZ as well as the US, Australia and Sweden. Our findings are also consistent with previous qualitative studies that have highlighted increasing awareness of the health risks of drinking, and the rise of ‘healthism’ in which health is positioned as a personal responsibility and a moral imperative [28,32].…”
Section: Discussionmentioning
confidence: 52%
“…In addition, some of the former functions of drinking (e.g., bonding with friends, meeting new people) are now being fulfilled online, thanks to the affordances of new communication technologies, coupled with the imperatives of neoliberalism (e.g., personal responsibility for one's future and avoidance of health risks). What remains unclear is whether the observed changes in priorities and practices of 14-17 year olds over the past 20 years reflect a unique generation who will maintain 'dry' throughout the life course, or merely a generation that is delaying alcohol use and will 'catch up' with previous generations by early adulthood [48,57,58]. New Zealand evidence suggests that binge drinking remains highly prevalent in early adulthood [59] and further research is needed to understand this transition.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, marked changes in youth drinking have also been observed and reported [26–28]. During this period, youth drinking has declined in several countries across the globe [29–31], in Sweden, the average consumption among ninth graders has more than halved since 2000 [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the new millennium adolescent drinking has undergone a dramatic decline in many European and English-speaking countries [7][8][9]. The reduced drinking is reflected in various measures of consumption, including age of initiation [10][11][12]. Sweden is among the countries that have experienced the largest declines [6].…”
Section: Introductionmentioning
confidence: 99%